Propolis of Apis mellifera from Yucatán, México: Study of biological properties - Kauich Kumul, Roger; Sauri Duch, Enrique; Toledo-López, Víctor; Acevedo Fernández, Juan José; Segura Campos, Maira (Ecosistemas y Recursos Agropecuarios, 2020)
Apis mellifera propolis has been used in ethnobotany and its compounds and therapeutic properties have been evaluated in various studies. Propolis from Maxcanú, Tizimín and Huhí, Yucatán, México were analyzed, determining the bioactive compounds (BC) of ethanolic extracts (PEE) and their potential use in the control of blood pressure, diabetes, and their antioxidant capacity. PEE was prepared by mixing 6 g of propolis with 20 mL of 95% ethanol, stirring daily for 28 days. BC were identified using HPLC and in vitro assays were performed on their antioxidant activity, ACE-I inhibition, and antidiabetic properties. Total phenols and flavonoids were between 1.27 ± 0.02 and 25.95 ± 0.99 mg GAE g−1 and 65.06 ± 3.48 and 85.64 ± 4.09 mg CE g−1 dry extract. The results of the in vitro assays were positive and a close relationship with the total content of flavonoids was detected, with epicatechin and p-coumaric being the main components identified. According to the results, the Huhí PEE had the highest values in all the assays, as well as the BC content. This study demonstrates that PEE can be used as a potential alternative in the treatment of certain diseases due to the therapeutic properties that exhibits.